Unraveling Complexity: A Strategy for the Characterization of Anisotropic Core Multishell Nanoparticles. (6th September 2020) - Lin, Wei; Greve, Christoph; Härtner, Sebastian; Götz, Klaus; Walter, Johannes; Wu, Mingjian; Rechberger, Stefanie; Spiecker, Erdmann; Busch, Sebastian; Schmutzler, Tilo; Avadhut, Yamini; Hartmann, Martin; et al.
Abstract: In this work, a widely applicable routine to characterize the core, surface, stability, and optical properties of CdSe/CdS/ZnS core–shell–shell nanorods after multiple growth steps is established. First, size, shape, and shell thickness of the nanorods are characterized by transmission electron microscopy (TEM), analytical ultracentrifugation (AUC), and small angle X‐ray/neutron scattering (SAXS/SANS). In the next step, Fourier‐transform infrared (FT‐IR) spectroscopy, thermogravimetric analysis (TGA), and SANS measurements are applied to determine the surface species of nanorods. Then, the colloidal stability of the nanorods is investigated by UV–vis spectroscopy and dynamic light scattering (DLS) after different washing cycles. Finally, photoluminescence quantum yield (PLQY) of the nanorods during washing and sample storage is determined. With this highly complementary routine for particle characterization, the core, surface, stability, and optical properties of nanorods after multiple growth steps are resolved. The results demonstrate the importance of the developed toolbox to characterize such highly complex, anisotropic nanorods for a technical environment. This is of major importance for the handling of colloidal quantum materials and their quality control in industrial applications. Abstract : The developed characterization strategy demonstrates the versatility and wide applicability in characterizing highly complex, anisotropic nanorods. The methodology can not only be regarded as blueprint for the multidimensional characterization of anisotropic colloidal nanorods with regard to quality control after synthesis but also is an important step toward a more effective formulation of nanomaterials.